From west to east: dissecting the global shift in inflammatory bowel disease burden and projecting future scenarios - Kaiqi Yang; Changhao Zhang; Rui Gong; Wei Jiang; Yuchen Ding; Yang Yu; Jinlong Chen; Min Zhu; Jiaxuan Zuo; Xueping Huang; Lumei Wang; Peng Li; et al. (BMC Public Health)
Abstract Background The epidemiology of inflammatory bowel disease (IBD) has changed dramatically worldwide. This survey analyzed patterns and trends in the burden of IBD to aid future decision making. Methods The incidence, prevalence, mortality, and disability-adjusted life year data for IBD were derived from the GBD (Global Burden of Disease) study. Results In 2021, there were 3,830,119 cases of IBD worldwide, including 375,140 new cases, 42,423 IBD-related deaths, and 1,510,784-year healthy life loss due to IBD. The burden of IBD is usually concentrated in regions and countries with high sociodemographic indices(SDI). In 2021, the number of cases (2,000,478) and deaths (22,968) in women were higher than those in men, but the number of new cases in men was higher (188,005 cases). At the global, regional, and national levels, the number of IBD-related illnesses and deaths is still slowly increasing, but the age-standardized rate(ASR) is on a downward trend. The decomposition analysis showed that the change in the burden of IBD was mainly due to the growth of the global population. Frontier analysis showed that age-standardized incidence rate(ASIR) were positively correlated with sociodemographic indexes. As SDI declines, IBD ASIR’s effective difference (EF) for a particular SDI is smaller. Conclusion As a major global public health issue, there are significant regional differences in the burden of IBD. There data are crucial for healthcare professionals, policymakers, and researchers to refine and enhance management strategies, aiming to further mitigate IBD ‘s global impact.